A Mixed‐Anion System Consisting of a Germyl Anion and Anions Delocalized on Conjugated Carbon Ring Skeletons. Issue 25 (21st March 2019) - Fujimori, Shiori; Mizuhata, Yoshiyuki; Tokitoh, Norihiro
Abstract: Invited for the cover of this issue is the group of Norihiro Tokitoh at Kyoto University. The image depicts a mixed‐trianion system based on a 9‐germaanthracene skeleton. Read the full text of the article at10.1002/chem.201900699 . Abstract : " Our main research interest is the elucidation of the similarities and differences in structures and reactivity between organic compounds and the corresponding heavier congeners. These studies are interesting and important from the standpoints of fundamental chemistry and open the way to more extensive application of main group chemistry ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 6284 ff. (DOI:10.1002/chem.201900699 ).